An Interdisciplinary Review of Language’s Power and Solidarity Investigation - Sinha, Ritu; Roy, Mamta (Journal of Advanced Research in English & Education; Vol 8 No 4 (2023): Journal of Advanced Research in English and Education, 2023)
Language is a dynamic and multifaceted tool that plays a pivotal role in shaping societal structures and interpersonal connections. This comprehensive review delves into the intricate interplay between power and solidarity within linguistic contexts, drawing upon a rich tapestry of theories and frameworks from linguistics, sociology, and communication studies. Examining both historical epochs and contemporary landscapes, the article sheds light on how language functions as a nuanced reflection of, and participant in, power dynamics. The exploration encompasses diverse facets, from the historical deployment of language to fortify or challenge societal hierarchies to contemporary issues arising in the digital age. By dissecting politeness theories, speech acts, and cross-cultural perspectives, the review navigates the complex terrain of language’s role in maintaining social harmony, negotiating power imbalances, and constructing collective identities. In addition to investigating linguistic markers of power, the article illuminates the equally vital concept of solidarity, probing the linguistic features that foster unity and cohesion in discourse. As we explore the nuances of shared language practices and their impact on group identity, a deeper understanding emerges of how language serves as both a mirror and a sculptor of social bonds. The review also delves into the global landscape, examining cross-cultural variations in the expression of power and solidarity. The challenges and opportunities inherent in intercultural communication are scrutinized, highlighting the need for a nuanced approach that acknowledges linguistic diversity. In the digital age, language’s influence on power dynamics has acquired new dimensions. The article scrutinizes the impact of digital communication on the negotiation of power in online spaces and its role in shaping public discourse and catalyzing social movements. As language continues to evolve in response to technological advancements, understanding its role in the contemporary socio-linguistic landscape becomes increasingly imperative.